Building partnership between employers and staff as a tool to enhance the competitivness of enterprise - Kovalchuk, Tatiana; Trygub, Inna (My University, 2015)
Partnerships between employers and workers are forming the sustainable competitive advantage of the company. These relations are based on the creation of mutually beneficial conditions. Enterprise used the most effective methods of personnel management, which can satisfy their needs. Workers make every effort to improve the performance and quality of work, customer satisfaction, leading to increased competitiveness.
Keywords: еconomy; development; company; resource; consumer; production; eкономіка; розвиток; компанія; ресурс; споживач; виробництво; развитие; кафедра ділової іноземної мови та міжнародної комунікації